Historical Study of the Neutrality Arrangements of the State Civil Apparatus in General Elections in Indonesia - Sarnawa, Bagus; Khaer, Fawaz Muhammad (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2000)
This research aims to determine the neutrality regulations of civil servants in general elections. To achieve this goal, analysis was carried out on secondary data or library materials consisting of primary legal materials, secondary legal materials, and tertiary legal materials. To complete secondary data, interviews were conducted with sources consisting of experts in the field of civil service law and general elections, as well as practitioners such as the State Civil Service Agency, the State Civil Service Commission, and the General Election Supervisory Agency of the Republic of Indonesia. This research applied a statute approach and combined it with a historical approach and a conceptual approach. The results of the research showed that from 1966 until now, the regulation of the neutrality of the State Civil Service in general elections has undergone changes in the subject and object of its regulation. However, this arrangement has not been able to guarantee the neutrality of the State Civil Service in general elections. This is inseparable from the political system, which does not yet support the realization of neutrality of the State Civil Service in General Elections.